Analysis of Customer Satisfaction in Case of the Day Center for the Elderly, Cluj-Napoca City Hall - Diana Gabriela REIANU (Transylvanian Review of Administrative Sciences, 2014)
This paper focuses on the analysis of customer satisfaction, being a research whose main purpose was to make an evaluation of social services offered to elderly people. The motivation of this study was to provide data for the organization in order to understand and increase the impact of its social products and services on the beneficiaries, to emphasize ways that can improve the organization’s mechanisms, to help the organization make the services suitable for its beneficiaries, and to take decisions regarding funding, customer needs and program improvement. The study focuses on the strengths and weaknesses within the studied organization based on the results obtained through the analysis of customer satisfaction in relation to the behavior and responsibility of the staff, to the quality of the services and to the variety of the activities that take place within the organization. The conclusions point out ways in which the organization can improve its services, emphasizing future directions of this study.